2022
DOI: 10.1007/s40801-022-00308-4
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Pattern of Monoamine Oxidase B Inhibitors Combined with Levodopa: A Retrospective Observational Analysis of Italian Healthcare Administrative Databases

Abstract: Background Parkinson’s disease is still incurable, and several factors are considered when defining pharmacological therapy. Objective The aim of this study was to describe the prescription pattern of monoamine oxidase B inhibitors (MAO-BIs) marketed in Italy (selegiline, rasagiline, safinamide) as an add-on to levodopa among new users of MAO-BIs, from the perspective of the Italian National Health Service. Patients and Methods Through cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…However, we cannot exclude the possibility that RBD was not detected as an AE signal in safinamide due to a small number of reports. Ronconi et al reported the prescription frequency of MAO-B inhibitors as 1059 patients used MAO-B inhibitors in 2017, 502 patients (47%) were selegiline, 161 patients (15%) were rasagiline, and 396 patients (37%) were safinamide in Italy 47 . Although the global prescription rate of MAO-B inhibitors is not reported, the reports for safinamide can be expected to increase.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude the possibility that RBD was not detected as an AE signal in safinamide due to a small number of reports. Ronconi et al reported the prescription frequency of MAO-B inhibitors as 1059 patients used MAO-B inhibitors in 2017, 502 patients (47%) were selegiline, 161 patients (15%) were rasagiline, and 396 patients (37%) were safinamide in Italy 47 . Although the global prescription rate of MAO-B inhibitors is not reported, the reports for safinamide can be expected to increase.…”
Section: Discussionmentioning
confidence: 99%